Unicompartmental and bicompartmental knee osteoarthritis show different patterns of mononuclear cell infiltration and cytokine release in the affected joints. (10th March 2015) - Moradi, B; Rosshirt, N; Tripel, E; Kirsch, J; Barié, A; Zeifang, F; Gotterbarm, T; Hagmann, S
Summary: It is still controversial which cell types are responsible for synovial inflammation in osteoarthritic (OA) joints. The aim of this study was to quantify the mononuclear cell populations and their cytokines in patients with different knee OA subtypes. Synovial membrane (SM), synovial fluid (SF) and peripheral blood (PB) were harvested from patients with unicompartmental (UC) and bicompartmental (BC) knee OA. Frequencies of mononuclear cells were assessed by flow cytometry in PB and SM. Naive SF samples were analysed for a broad variety of cytokines by multiplex analysis. SM of both groups displayed a distinct mononuclear cell infiltration, with CD14 + macrophages being the major cell population, followed by CD4 + T cells and only small numbers of CD8 + T, CD19 + B and CD16 + CD56 + natural killer (NK) cells. Between the two groups, SM of BC OA showed significantly higher amounts of mononuclear cells (135·7 ± 180 versus 805 ± 675 cells/mg, P = 0·0009) and higher CD4 + T cell presence (3·4 ± 4·6 versus 9·1 ± 7·5%, P = 0·0267). SF of BC OA displayed significantly higher concentrations for a number of proinflammatory cytokines [CXCL1, eotaxin, interferon (IFN)-γ, interleukin (IL)-7, IL-8, IL-9, IL-12]. UC and BC OA show significant differences in their synovial inflammatory pattern. Whereas in UC OA CD14 + macrophages are the predominant cell population, BC OA has a higher inflammatory profile and seems to be driven by CD14 + macrophages and CD4 + T cells. Inclusion of clinical information into the analysis of cellular and molecular results is pivotal in understanding the pathophysiology of OA.